O Pagador de Promessas, de Dias Gomes: um estudo de elementos do trágico no drama brasileiro. - Rocha, Eduardo Sousa (2024)
O Pagador de Promessas is Dias Gomes’ most celebrated work and, furthermore, it has stablished itself as one of the greatest successes in Brazilian theater. The playwright tells the story of Zé do Burro, a simple man from the sticks who promises to carry a cross on his back from the farm where he lives, in the countryside, to the church of St. Barbara, in Salvador, aiming to save his pet donkey. Based on the premise that Zé do Burro’s journey is related to the Greek theater, this dissertation seeks to identify elements of the tragic in Dias Gomes’ O Pagador de Promessas, articulating shape and content to, in addition, discuss thematic issues connected to the drama, namely: examining the relationships of the characters with the senses of sacred and the unburied body. As an attempt to achieve these goals, the work resorts to bibliographic research, based on works of literary, theatrical, historical, anthropological, and philosophical theory and criticism by authors such as Aristotle, Albin Lesky and Anatol Rosenfeld. As for the methodological proceedings of research, this work seeks to explore aspects of character analysis, historical context, as well as comparative reading with the Greek tragedy Antigone, by Sophocles, supported by the theory of intertextuality from scholars such as the author Tiphaine Samoyault.